HYDRODESULFURIZATION OF CRUDE OIL FRACTIONS USING Co-Mo/Al2O, CATALYST - A.S. Nasution (Scientific Contributions Oil and Gas, 1989)
Kinetic of hydrodesulfurization reaction is studied for crude oil fractions: Vacuum distillate, deasphalted oil, reduced crude oil and vacuum residue